2017
DOI: 10.1016/j.algal.2017.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Nutrients from anaerobic digestion effluents for cultivation of the microalga Nannochloropsis sp. — Impact on growth, biochemical composition and the potential for cost and environmental impact savings

Abstract: Microalgal biotechnology has yielded a range of products for different consumer markets, but large scale production for bulk commodities is limited by the cost and environmental impact of production. Nutrient requirements for large-scale production contribute significantly to the cost and environmental impact of microalgal biomass production and should subsequently be addressed by more careful sourcing of nutrients. This study assessed the use of nitrogen and phosphorus contained in effluents from anaerobic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 73 publications
(116 reference statements)
0
19
0
Order By: Relevance
“…Liquid digestate from methane fermentation of maize silage can be used as a substitute growth medium for A. protothcoides. In the study conducted by Mayers et al [20], effluents of anaerobically digested food waste were estimated as a potential nitrogen and a phosphorus source. The results of the studies demonstrate that a suitable dilution of this effluent could meet the nitrogen demands and, partially, the phosphorus demands of Nannochloropsis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liquid digestate from methane fermentation of maize silage can be used as a substitute growth medium for A. protothcoides. In the study conducted by Mayers et al [20], effluents of anaerobically digested food waste were estimated as a potential nitrogen and a phosphorus source. The results of the studies demonstrate that a suitable dilution of this effluent could meet the nitrogen demands and, partially, the phosphorus demands of Nannochloropsis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen can account for 10% or more of the dry weight of algae, depending on the species and N availability for microalgal cells. Its availability is an important determinant of the lipid accumulation process in cells [20]. Liquid digestate fractions are primarily a source of inorganic N (mainly NH 4 ) and P-PO 4 [20].…”
Section: Discussionmentioning
confidence: 99%
“…Nannochloropsis sp. (CCAP211/78) was cultivated according the methods used for strain maintenance and flask cultivation detailed in Mayers et al (45). Cultures were allowed to deplete media nitrogen for the purposes of this analysis to generate cells with higher lipid content.…”
Section: Cell Culturementioning
confidence: 99%
“…Although lipid droplets in microalgae are to date not well understood (54), it has been found that the cellular lipid storages in Nannochloropsis increase, in size and number, under nitrogen depletion (55). It has also been shown that the same strain of microalgae grown under nitrogen starvation contains around 15.0±1.3% saturated fatty acids and 21.2±1.7 % unsaturated fatty acids (45). This results in an average chain length of 16.9 with 1.4 double bonds.…”
Section: In Situ Lipid Mappingmentioning
confidence: 99%
“…Therefore, this work reports on a pilot scale waste based biorefinery approach, utilising formulated digested agricultural streams as growth media, suitable for mass cultivation of industrially significant microorganisms, associated with chemicals and fuels production. Within this concept and to test its usefulness, two well known [20,21] autotrophic microalgae namely Nannochloropsis oceanica and Scenedesmus quadricuada were grown on treated digested agricultural wastewater of specific N:P ratio on a 800 L photobioreactor (PBR). The effluents were physico-chemically characterised and treated through membrane filtration to produce a balanced composition of nitrogen and phosphate effluent suitable for autotrophic algal cultivation.…”
Section: Introductionmentioning
confidence: 99%